Auto-ponderomotive beam guiding up to 9.5 keV - Schmidt-Kaler, Franz; Walther, J.; Seidling, Michael; Zimmermann, Robert; Hommelhoff, Peter (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2025)
We report successful electrostatic auto-ponderomotive (APE) electron beam guiding at electron energies of up to ⁠. We do so with electrons derived from a scanning electron microscope and demonstrate the guiding along an S-shaped trajectory. For this S-shaped guide, we use a mirror-symmetrical double-planar electrode layout and apply static voltages only. We study details of the APE guiding process and show that we can extend its operability over almost three orders of magnitude in beam energy. In particular, we reach a range of electron energies often used in conventional scanning electron microscope
Keywords: Ponderomotive force; Electron beam processing; Electro-optics; Scanning electron microscopy; Interaction-free measurement

Beam splitting of low-energy guided electrons with a two-sided microwave chip - Zimmermann, Robert; Weber, Philipp; Seidling, Michael; Hommelhoff, Peter (Applied Physics Letters, 2019)
We present a two-layer design and experimental demonstration of a chip-based electron beam splitter working for electron energies up to 200 eV. Beam splitting arises from smoothly transforming the transverse microwave guiding potential from a single-well into a double-well, thereby generating two separated output beams. We discuss future structures for coherent electron beam splitting, which would pave the way for an electron interferometer on a chi
Keywords: chip based electron splitter; quantum microscope; electron microscopy

Charged particle guiding and beam splitting with auto-ponderomotive potentials on a chip - Zimmermann, Robert; Seidling, Michael; Hommelhoff, Peter (Nature Communications, 2021)
Electron and ion beams are indispensable tools in numerous fields of science and technology, ranging from radiation therapy to microscopy and lithography. Advanced beam control facilitates new functionalities. Here, we report the guiding and splitting of charged particle beams using ponderomotive forces created by the motion of charged particles through electrostatic optics printed on planar substrates. Shape and strength of the potential can be locally tailored by the lithographically produced electrodes’ layout and the applied voltages, enabling the control of charged particle beams within precisely engineered effective potentials. We demonstrate guiding of electrons and ions for a large range of energies (from 20 to 5000 eV) and masses (from 5 · 10−4 to 131 atomic mass units) as well as electron beam splitting for energies up to the keV regime as a proof-of-concept for more complex beam manipulation.<br
Keywords: electron optics; electron beam splitter; ponderomotive forces

Chip-based electrostatic beam splitting of guided kiloelectron volt electrons - Seidling, Michael; Zimmermann, Robert; Hommelhoff, Peter (Applied Physics Letters, 2021)
We present a beam splitter for guided electrons using an electrostatic guiding potential created above the surface of two opposing planar microstructured printed circuit boards. The electric fields acting on the electrons result in a ponderomotive potential. We show that we can smoothly transition the ponderomotive potential from a single-well into a double-well, which leads to the splitting of the electron beam. Efficient beam splitting is observed over a large range of kinetic energies starting at 200 eV up to 1700 eV. We discuss future work needed to reach adiabatic beam splitting for quantum state-selective electron optics. This will pave the way for an electron interferometer on a chip and, therefore, result in until now not possible elements for electron optics and microscopy.<br
Keywords: electron optics; electron beam splitter; ponderomotive potential; adiabatic beam splitting; Quantum Electron Microscope

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec

Planar On-Chip Auto-Ponderomotive Devices for Electron Beam Control - Schmidt-Kaler, Franz; Seidling, Michael; Zimmermann, Robert; Bode, Nils; Bammes, Fabian; Radtke, Lars; Hommelhoff, Peter (2024 37th International Vacuum Nanoelectronics Conference (IVNC), 2024)
New means to manipulate electron beams are highly sought after as they might enable new electron optical functionalities and devices. We recently demonstrated guiding of electron beams with energies of up to 4 keV with the help of a transversely confining potential akin to that of a Paul trap. It resulted from a periodic arrangement of electrodes with alternating polarity, leading to an oscillatory field of the moving electrons. We call this scheme auto-ponderomotive electron guiding. With a more refined electrode pattern, we could also demonstrate splitting of the guided electron beam. The focus of the presentation will be on a resonator for guided electrons, consisting of a linear guide and two switchable electron mirrors. With these elements demonstrated, we aim for quantum electron microscope operation.<br
Keywords: Electrodes; Electron traps; Electron beams; Optical switches; Optical resonators; Electron optics; System-on-chip

Resonating Electrostatically Guided Electrons - Seidling, Michael; Schmidt-Kaler, Franz; Zimmermann, Robert; Simonaitis, J. W.; Keathley, P. D.; Berggren, Karl K.; Hommelhoff, Peter (Physical Review Letters, 2024)
An essential component for quantum-enhanced measurements with free electrons is an electron resonator. We report stable guiding of free electrons at 50 eV energy for up to seven round trips in a linear autoponderomotive guiding structure, which is realized with two microstructured printed circuit boards that generate the required electromagnetic fields. Free electrons are laser triggered from a sharp tungsten needle tip and coupled in at the front of the electron resonator with the help of sub-nanosecond-fast switchable electron mirrors. After a variable time delay, we open the rear electron mirror and measure the number of trapped electrons with a delay-line detector. We demonstrate, simulate, and show ways of optimizing an electron resonator in simulations, which will help enable “interaction-free” measurement setups, including multipass and quantum-Zeno effect based schemes, helping to realize the quantum electron microscope.<br